Prediksi Financial Distress Pada Perusahaan Sektor Property dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Hanifah Martini; Rianti Setyawasih (Formosa Journal of Sustainable Research, 2022)
This study aims to prove the ability of financial rations in measuring financial distress. The financial ratios used in this study are return on assets, current ratio, debt to assets ratio, and total assets turnover in property and real estate companies listed on the Indonesia Stock Exchange (IDX) period 2017-2020. The research sample was determined by purposive sampling method and Z’-Score with  < 1,23 that obtained 66 data. The data used in the form of secondary data from www.idx.co.id. The method used is multiple linear regression analysis. According to the results of research that has been done, the variabels of are ROA, CR, and TATO had a significant adverse effect, while variabel DAR had a significant positive effect on financial distress